Nuclear cardiac imaging for the assessment of myocardial viability - Slart, R.H.J.A. (2005)
An important aspect of the diagnostic and prognostic work-up of patients with ischaemic cardiomyopathy is the assessment of myocardial viability. Patients with left ventricular dysfunction who have viable myocardium are the patients at highest risk because of the potential for ischaemia but at the same time benefit most from revascularisation. It is important to identify viable myocardium in these patients, and radionuclide myocardial scintigraphy is an excellent tool for this. Single-photon emission computed tomography perfusion scintigraphy (SPECT), whether using (201)thallium, (99m)Tc-sestamibi, or (99m)Tc- tetrofosmin, in stress and/or rest protocols, has consistently been shown to be an effective modality for identifying myocardial viability and guiding appropriate management. Metabolic and perfusion imaging with positron emission tomography radiotracers frequently adds additional information and is a powerful tool for predicting which patients will have an improved outcome from revascularisation. New techniques in the nuclear cardiology field, such as attenuation corrected SPECT, dual isotope simultaneous acquisition (DISA) SPECT and gated FDG PET are promising and will further improve the detection of myocardial viability. Also the combination of multislice computed tomography scanners with PET opens possibilities of adding coronary calcium scoring and noninvasive coronary angiography to myocardial perfusion imaging and quantification.